2022
DOI: 10.3390/jrfm15060252
|View full text |Cite
|
Sign up to set email alerts
|

Budgetary Allocations and Government Response to COVID-19 Pandemic in South Africa and Nigeria

Abstract: The eruption of the novel virus brought to the global scene the prediction that Africa would be worse hit by the pandemic. This prediction was partly built on the widely recognized fact that Africa is the continent with the weakest public health care system and the lowest budgetary allocations to health. However, contrary to this prediction, the COVID-19 death rate in Africa has been low compared to in other continents. Debates on Africa’s low COVID-19 death rate have generated mixed reactions, the majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, to sustain this effort, results from the study indicated that it is crucial to continue encouraging and creating continuity in the training of the LF program and response staff. The sustainability of LF programs and interventions, as revealed by the results, is dependent on trust building, prudent financial management, and strong human resource capacities and commitments 74 which is the goal of the government policy direction.…”
Section: Dovepressmentioning
confidence: 99%
“…However, to sustain this effort, results from the study indicated that it is crucial to continue encouraging and creating continuity in the training of the LF program and response staff. The sustainability of LF programs and interventions, as revealed by the results, is dependent on trust building, prudent financial management, and strong human resource capacities and commitments 74 which is the goal of the government policy direction.…”
Section: Dovepressmentioning
confidence: 99%
“…With regard to budgetary responses to the COVID-19 crisis in emerging economies, the literature highlighted that existing issues like healthcare facilities, poverty, unemployment, inequalities, and fiscal instability all meant governments were faced with even more challenges, especially when they opted for strict travel restrictions (Chukwudi and Victor, 2022;Desdiani et al, 2022). India, for instance, experienced an economic slowdown prior to the COVID-19 crisis which meant that the government operated in a tight fiscal space in response to the crisis.…”
Section: Patterns Of Budgetary Responses and Its Challenges During Co...mentioning
confidence: 99%
“…The COVID-19 pandemic presented health, security, and socio-economic problems, and disrupted life worldwide. It was a crisis with many complexities (Chukwudi and Victor, 2022). The unprecedented impact of the COVID-19 crisis exposed flawed policies in many sectors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Developing countries faced particular challenges in responding to the pandemic although were spared the worst impacts despite weaker health care systems and lower budgetary resources. Chukwudi and Victor (2022) examine the response in South Africa and Nigeria through budget revisions. Both countries adjusted their budgets, but South Africa allocated more funds to government agencies in charge of COVID-19 and various relief packages than Nigeria.…”
Section: Lessons From the Covid-19 Crisismentioning
confidence: 99%
“…In addition to a systemic recovery of the global economy and society, the analysis underlying policy also requires a systemic recovery as the limitations of many frameworks and models has been exposed. This requires more real-time analytics to address crises in real time (Rigobon et al 2022), more inter-disciplinary analysis and in particular the integration of economics and epidemiology (Lipton and Lopez de Prado 2022), understanding the impacts of the pandemic in developing countries (Chukwudi and Victor 2022), and the drivers of policies to limit the spread of COVID-19 (Bourdin et al 2022). Finally, it requires an agenda for implementing and communicating resilience (Betts and Buzzanell 2022).…”
Section: Introductionmentioning
confidence: 99%